Новый вид жука-щелкуна рода Pseudanostirus Dolin (Coleoptera, Elateridae) из Казахстана - Долин, В.Г.; Гурьева, Е.Л. (Вестник зоологии, 1988)
P. bicolor, sp. n. is described on a single holotype male specimen; similar to P. altaicus · (E s c h.), but good eliffers by color and form of pronotum, antennae and aoedeagus; East Kazakhstan, spurs of the Tarbagatai Mountain range, Urdzhar. Deposited in the collection of Schmalhausen Institute of Zoology (Kiev).